Effect of Food, Antacid, and Age on the Pharmacokinetics of the Oral Thrombin Receptor Antagonist Vorapaxar (SCH 530348) in Healthy Volunteers. Issue 3 (14th May 2013) - Kosoglou, Teddy; Reyderman, Larisa; Tseng, Jack; Kumar, Bharath; Xuan, Fengjuan; Schiller, James; Meehan, Alan G.; Kim, Kenneth; Cutler, David L.
Abstract This randomized, open‐label, parallel group study examined the effects of food, antacid, and age on the pharmacokinetics of vorapaxar. In total, 101 subjects were enrolled including 83 young adults (18–45 years) and 18 elderly subjects (>65 years). Subjects received single‐dose vorapaxar 40 mg after a 10‐hour fast (young and elderly) or with extra‐strength antacid, food, or 1 or 2 hours after food (young only). Vorapaxar 40 mg was rapidly absorbed after a fast (median Tmax: 1 hour). Administration with food or 1 or 2 hours post‐meal modestly increased vorapaxar mean area under the curve (AUC) and Cmax and prolonged median Tmax by 1 hour. Concomitant food modestly increased vorapaxar AUC from time zero to infinity [AUC(I)] and Cmax 43% and 31%, respectively. Antacid modestly decreased vorapaxar AUC(I) by 15% and Cmax by 38%, and increased median Tmax by 1 hour. Vorapaxar AUC(I) and Cmax were 41% and 29% higher, respectively, in elderly versus young subjects. Concomitant food and older age were associated with modest increases, and antacid was associated with a small decrease in vorapaxar exposure, which are not expected to affect the drug's safety or efficacy.